2010
DOI: 10.1373/clinchem.2010.147660
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pregnancy-Associated MicroRNAs in Maternal Plasma

Abstract: BACKGROUND:Several placental microRNAs (miRNAs) have been identified as pregnancy-associated molecules with the potential for use in estimating the condition of the placenta. Our understanding of these novel molecules is still limited, however. The aim of this study was to isolate and characterize pregnancyassociated miRNAs in maternal plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
178
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(190 citation statements)
references
References 15 publications
7
178
0
5
Order By: Relevance
“…Chim et al (2008) identified 17 out of 157 miRNAs in significantly higher concentrations in normal placentas than in maternal blood cells and the 4 most abundant placental miRNAs (miR-141, miR-149, miR-299-5p, and miR-135b) in maternal plasma samples. Similarly, in another study, Miura et al (2010) identified 24 pregnancy-associated miRNAs. However, the investigators finally selected, for further analysis, only 5 miRNAs (miR-515-3p, miR-517a, miR-517c, miR518b, and miR-526b) that showed a significant increase in maternal plasma concentrations through gestation and a significant decrease after pregnancy termination.…”
Section: Detection Of Placental-specific Mirnas In Maternal Circulationmentioning
confidence: 81%
“…Chim et al (2008) identified 17 out of 157 miRNAs in significantly higher concentrations in normal placentas than in maternal blood cells and the 4 most abundant placental miRNAs (miR-141, miR-149, miR-299-5p, and miR-135b) in maternal plasma samples. Similarly, in another study, Miura et al (2010) identified 24 pregnancy-associated miRNAs. However, the investigators finally selected, for further analysis, only 5 miRNAs (miR-515-3p, miR-517a, miR-517c, miR518b, and miR-526b) that showed a significant increase in maternal plasma concentrations through gestation and a significant decrease after pregnancy termination.…”
Section: Detection Of Placental-specific Mirnas In Maternal Circulationmentioning
confidence: 81%
“…This step is further followed by a validation procedure, frequently RT-qPCR, with additional samples from PE cases and controls. Usually, the second step does not completely validate the profiling step (18,20,21). Thus, in order to evaluate previously differentially reported miRNAs in PE, we performed a case-control study with 23 PE patients and 44 controls.…”
Section: Discussionmentioning
confidence: 99%
“…They are critical in many biological processes, including the regulation of cell differentiation, proliferation, apoptosis, angiogenesis, and metabolism (17). Specific plasma-related miRNAs were identified in maternal plasma or serum in normal pregnancies, as well as in pathological pregnancy conditions, such as PE (18,19). Several recent reports described the significant dysregulation of specific miRNA expression in the maternal circulation of PE patients compared with controls (miR-24, miR-26a, miR-29a, miR-103, miR-130b, miR-141, miR-144, miR-152, miR-181a, miR-210, miR-342-3p, miR-520, miR-574-5p, and miR-1233) (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies provided biological insight, their clinical utility is limited by the necessity of obtaining placental tissue after delivery. Attempts to detect plasma miRNAs in maternal plasma have thus far been limited to microarray and quantitative RT-PCR approaches (28,37). Detecting placental miRNAs by deep sequencing could direct specific noninvasive diagnosis of these diseases of pregnancy.…”
mentioning
confidence: 99%